Respiratory muscle weakness increases dead‐space ventilation ratio aggravating ventilation–perfusion mismatch during exercise in patients with chronic heart failure. Issue 2 (14th November 2018) - Hamazaki, Nobuaki; Masuda, Takashi; Kamiya, Kentaro; Matsuzawa, Ryota; Nozaki, Kohei; Maekawa, Emi; Noda, Chiharu; Yamaoka‐Tojo, Minako; Ako, Junya
ABSTRACT: Background and objective: Respiratory muscle weakness causes fatigue in these muscles during exercise and thereby increases dead‐space ventilation ratio with decreased tidal volume. However, it remains unclear whether respiratory muscle weakness aggravates ventilation–perfusion mismatch through the increased dead‐space ventilation ratio. In ventilation–perfusion mismatch during exercise, minute ventilation versus carbon dioxide production (VE/VCO2 ) slope > 34 is an indicator of poor prognosis in patients with chronic heart failure (CHF). We examined the relationship of respiratory muscle weakness with dead‐space ventilation ratio and ventilation–perfusion mismatch during exercise and clarified whether respiratory muscle weakness was a clinical predictor of VE/VCO2 slope > 34 in patients with CHF. Methods: Maximal inspiratory pressure (PImax ) was measured as respiratory muscle strength 2 months after hospital discharge in 256 compensated patients with CHF. During cardiopulmonary exercise test, we assessed minute dead‐space ventilation versus VE (VD/VE ratio) as dead‐space ventilation ratio and VE/VCO2 slope as ventilation–perfusion mismatch. Patients were divided into low, moderate and high PImax groups based on the PImax tertile. We investigated determinants of VE/VCO2 slope > 34 among these groups. Results: The low PImax group showed significantly higher VD/VE ratios at 50% of peak workload and at peak workload and higher VE/VCO2 slope than the other two groups ( P < 0.001, respectively). PImax was a significant independent determinant of VE/VCO2 slope > 34 (odds ratio (OR): 0.67, 95% CI: 0.54–0.82) with area under the receiver operating characteristic curve of 0.812 (95% CI: 0.750–0.874). Conclusion: Respiratory muscle weakness was associated with an increased dead‐space ventilation ratio aggravating ventilation–perfusion mismatch during exercise in patients with CHF. Abstract : Respiratory muscle weakness is often detected in patients with chronic heart failure (CHF). During exercise, we demonstrate that respiratory muscle weakness is associated with increased dead‐space ventilation ratio and higher ventilation–perfusion mismatch. Our findings indicate that respiratory muscle weakness complicates CHF; possibly causing abnormal ventilation during exercise.